APLIKASI SIG UNTUK PENYUSUNAN RENCANA KONTINJENSI DAERAH RAWAN LONGSOR DI KECAMATAN KOKAP, KABUPATEN KULON PROGO - , RR.SUSPIMA WULANDARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Kokap subdistrict, Kulon Progo is one of the areas in Indonesia which has landslide vulnerability. Based on the 2007 until 2012 published by Kulon Progo Badan Penanggulangan Bencana Daerah (BPBD), there were several landslidesoccured in Kokap which resulted in many negative impacts. Contingency Plan can be used to reduce the impacts. It can be complemented with risk map which shows the condition of landslide susceptibly. Using the Geographic Information System (GIS), the risk map is created. The aim of this research is to create contingency plan which is used to decrease the disaster risk caused by landslide.Contingency planis a documentsconsists ofscenariosandsystemstorespond to disasterin order toreduce impact disasters. This research employed the following dataset: soil map, pebbles map, landuse map, rainfall map, and contour map. They constitute the common factors of landslide. Quantum GIS software was used for data processing. The contour map was transformed into slope map. Then it was used to weight the influencing factors. These five factors were weighted and overlaid. The results were classified into three landslide susceptibility levels, low, medium, and high. Field surveys wereconducted to check the result from GIS processing Contingency plan was created in the area with the highest susceptibility level. The research results show that in Kokap subdistrict the highest landslide susceptibility area covers 2432.84 Hectares. Two villages with the highest score of susceptibility are Hargotirto and Kalirejo. Medium landslide susceptibility covers area of 3826.02 Hectares. Low landslide susceptibility covers area of 520.47 Hectares. The field survey consisted a visit to 34 points. There were 29 points are matched with the map and five were not matched. Based on the research results, Hargotirto village had thehighest landslide susceptibility area